Dopamine D1-like receptor signalling in the hippocampus and amygdala modulates the acquisition of contextual fear conditioning - Heath, Florence C.; Jurkus, Regimantas; Bast, Tobias; Pezze, Marie A.; Lee, Jonathan L.C.; Voigt, Jörg-Peter; Stevenson, Carl W. (Springer, 2015)
RATIONALE: Dopamine D1-like receptor signalling is involved in contextual fear conditioning, but the brain regions involved and its role in other contextual fear memory processes remain unclear.